HUBUNGAN ANTARA INDEKS MASSA TUBUH (IMT) DENGAN KADAR GULA DARAH PADA KOMUNITAS LANSIA WANITA DI DAHLIA SENJA LIMO, DEPOK - Nadira Alifia Puteri Hariyanto (2023)
Elderly is a natural life process which is marked by the aging process when someone reaches the age of 60 years and over. Diabetes mellitus describes a group of metabolic diseases, the common finding of which is elevated blood glucose levels (hyperglycemia). One of the causes of an increase in blood glucose levels is the Body Mass Index (BMI). This study aims to determine the relationship between body mass index (BMI) and blood glucose levels (GDS) in the Dahlia Senja elderly female community. This type of research is analytic with cross sectional approach and survey method. The research sample is 40 elderly women at Dahlia Senja. Sampling with Total Sampling method. Primary data that has been obtained from BMI measurements and checking blood sugar levels when then analyzed using the Spearman Correlation statistical test. Keywords: Body Mass Index, Elderly, Blood Glucose